ANALYSIS OF THE ROLE OF INTERCULTURAL ONLINE LEARNING FOR STUDENTS IN THE ONLINE INDEPENDENT STUDENT EXCHANGE (PMM) PROGRAM - Suci Rahmadani; Kamil; Latifah Hannum; Nabila Dwi Alhusna; Nur Innayah; Gilang Purnama; Ulul Amri (International Journal of Society and Law, 2025)
This study aims to analyze the role of intercultural online learning for students in the online Independent Student Exchange Program (PMM). The method used is a library research with a descriptive qualitative approach. Data was obtained from various literature sources such as scientific journals, academic books, policy documents, and PMM implementation reports. The results of the study show that online learning between cultures through the Nusantara Module has an important role in forming tolerance attitudes, increasing cross-cultural understanding, and strengthening national values among students. Even though it is carried out online, virtual interactions between students from various regions are still able to create a meaningful and inclusive learning experience. However, challenges such as technological limitations and barriers to cultural communication are aspects that need to be overcome. In conclusion, intercultural online learning in online PMM makes a positive contribution to strengthening the character of student diversity, and needs to continue to be developed through innovative and interactive learning strategies.